2013
DOI: 10.3109/09687637.2013.812614
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of concurrent alcohol, tobacco, and cannabis use in Germany: Prevalence and correlates

Abstract: Aims: This study investigated past month patterns and risk factors of alcohol, tobacco and cannabis use by level of intensity in the German general population. Methods: Data from the 2006 German Epidemiological Survey of Substance Abuse (ESA) were used. The cross-sectional random sample consisted of N ¼ 7912 adults aged 18-64 years. The response rate was 45%. Intensive use of each substance was measured applying substance-specific cut-off points: alcohol: 420/30 g pure ethanol daily for women/men; tobacco: 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
2
18
1
1
Order By: Relevance
“…Furthermore, it should be noted that the prevalence alone does not reveal the harmfulness of polydrug use; rather, additional factors such as the intensity of use or potential harms of combining different substances need to be taken into consideration [12,13]. One possibility to measure SPU in population surveys would be to include questions concerning, for instance, different combinations of substances used at the same time or in temporal proximity, frequency and motivation of such use as well as perceived harms of SPU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it should be noted that the prevalence alone does not reveal the harmfulness of polydrug use; rather, additional factors such as the intensity of use or potential harms of combining different substances need to be taken into consideration [12,13]. One possibility to measure SPU in population surveys would be to include questions concerning, for instance, different combinations of substances used at the same time or in temporal proximity, frequency and motivation of such use as well as perceived harms of SPU.…”
Section: Discussionmentioning
confidence: 99%
“…Polydrug use is noted especially among problem drug users [6,7], but it needs to be recognized among the general population too due to its serious health and social consequences [8,9,10]. In the present literature, it is often claimed that polydrug use has increased during the last decades [11,12,13]. However, as far as the authors know, only a few studies have presented research evidence about prevalence trends of polydrug use among the general population [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found only three general population studies of simultaneous use among adults (Höhne et al, 2014; Midanik et al, 2007; Norton and Colliver, 1988). First, an older study using the 1982 National Household Survey on Drug Abuse data (N=5,624) showed that individuals who combined cannabis and alcohol were more likely to be male and in the 18–34 age group than not (Norton and Colliver, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In the 2000 National Alcohol Survey (N=7,612), simultaneous use was related to increased social consequences, depression and alcohol dependence compared to alcohol-only users, and that simultaneous users were younger, less educated, less likely to have a partner, and had heavier drinking patterns (Midanik et al, 2007); the authors did not make direct comparisons between simultaneous and concurrent users. Most recently, an epidemiologic study of German adults (N=7,912) showed that male gender, older age, less education, and having a substance use disorder all significantly predicted multiple intensive substance use (use of cannabis, alcohol and/or tobacco above a pre-defined threshold) compared to non- or single-intensive substance use (Höhne et al, 2014). …”
Section: Introductionmentioning
confidence: 99%